A New History of Kentucky - Klotter, James C.; Friend, Craig Thompson (University Press of Kentucky, 2018)
This volume includes an overview of the state and its economic, educational, environmental, racial, and religious histories. At its essence, Kentucky's story is about its people - not just the notable and prominent figures but also lesser-known and sometimes overlooked personalities. The human spirit unfolds through the lives of individuals such as Shawnee peace chief Nonhelema Hokolesqua and suffrage leader Madge Breckinridge, early land promoter John Filson, author Wendell Berry, and Iwo Jima flag-raiser Private Franklin Sousley. They lived on a landscape defined by its topography as much as its political boundaries, from Appalachia in the east to the Jackson Purchase in the west, and from the Walker Line that forms the Commonwealth's southern boundary to the Ohio River that shapes its northern boundary. Along the journey are traces of Kentucky's past - its literary and musical traditions, its state-level and national political leadership, and its basketball and bourbon. Yet this volume also faces forthrightly the Commonwealth's blemishes - the displacement of Native Americans, African American enslavement, the legacy of violence, and failures to address poverty and poor health.--description provided by publisher.